MODEL RANCANGAN SISTEM INFORMASI PROJECT MONITORING - Yanti, Yanti (Bina Nusantara University, 2009)
Economic development makes the property industry growing very rapidly. The property development is supported by the development of contractor’s company that conducts property development. Inside the contracting company doing business can not perform their own procurement because of the many items that must be provided. For the purposes of the construction company entered into an agreement with the subcontractor as vendor conduct procurement in accordance with the needs of contracting companies. To simplify the procurement process, generally conducted by a process called a tender / auction. This is done by contracting companies to get quality and price in accordance with the desired budget. The company’s commitment subcontractors as the procurement of goods to be one key to successful contracting company doing business development process. Therefore, the subcontractor companies are required to have a good commitment. Therefore we need a project monitoring system that can monitor business processes running on those sub contractor company. The purpose of this research is to design a project monitoring information system in accordance with company requirements to operational activities more effective and efficient company.Keywords: project monitoring, design model, subcontractor